Papillary renal cell carcinoma with prominent spindle cell stroma - tumor mimicking mixed epithelial and stromal tumor of the kidney: Clinicopathologic, morphologic, immunohistochemical and molecular genetic analysis of 6 cases - Rogala, Joanna; Kojima, Fumiyoshi; Alaghehbandan, Reza; Agaimy, Abbas; Martinek, Petr; Ondic, Ondrej; Ulamec, Monika; Sperga, Maris; Michalova, Kvetoslava; Pivovarcikova, Kristyna; Pitra, Tomáš; Hora, Milan; et al. (Annals of Diagnostic Pathology, 2020)
Papillary renal cell carcinoma (PRCC) is currently a well-studied type of RCC. In addition to PRCC type 1, there are a number of other subtypes and variants of PRCCs which have been reported. We describe a series of 6 PRCCs with papillary, micropapillary and/or tubulopapillary architecture and prominent spindle cell stroma, resembling stroma in mixed epithelial and stromal tumor of the kidney (MESTK) or sarcomatoid RCC. Clinicopathologic, morphologic, immunohistochemical and molecular features were analyzed. All patients were males with an age range of 44–98 years (mean 65.3, median 65.5 years). Tumor size ranged from 2.4–11.4 cm (mean 5.8, median 4.5 cm). Follow-up data were available for 4 patients, ranging from 3 to 96 months (mean 42.75, median 36 months). Epithelial cells were mostly cylindrical with eosinophilic cytoplasm, showing nuclear grade 2 and 3 (ISUP/WHO). In all cases, loose to compact prominent stroma composed of spindle cells, without malignant mesenchymal heterologous elements was detected. No atypical mitoses were found, while typical mitoses were rare in both epithelial and stromal components. Epithelial cells were positive for CK7, AMACR, and vimentin in all cases, while negative for TFE3, HMB45, desmin, CD34, and actin. The stroma was positive for vimentin, actin and focally for CD34, while negative for CK7, AMACR, TFE3, HMB45, and desmin. Estrogen and progesterone receptors were completely negative. FH and SDHB expression was retained in all analyzable cases. Proliferative index was barely detectable in stromal component and low in epithelial component, ranging 0 to 5% positive stained cells/high power field. Copy number variation was variable with no distinct pattern. No mutations in CDKN2A, BAP1, MET were detected. PRCC with MESTK-like features is a distinct variant of PRCC mimicking MESTK. Our findings add to the body of literature on ever expanding variants of PRCCs. Both epithelial and stromal components lacked true Müllerian features, which was also proven by immunohistochemistry.
CRIS-Team Scopus Importer:2019-12-24
Keywords: Kidney; MESTK-like; Papillary renal cell carcinoma; Sarcomatoid-like